2016
DOI: 10.18632/oncotarget.12523
|View full text |Cite
|
Sign up to set email alerts
|

Human cytomegalovirus infection and colorectal cancer risk: a meta-analysis

Abstract: Human cytomegalovirus infection (HCMV) has been recently considered as a factor for tumorigenesis. The current study used meta-analytical techniques to explore the prevalence of HCMV in tumor tissues and the relationship between human cytomegalovirus and colorectal cancer (CRC) risk. 11 studies detecting HCMV DNA in tumor tissues were included in meta-analysis. The prevalence rate and odds ratio (OR) were two main parameters. The overall prevalence of human cytomegalovirus DNA in tumor tissues were 27.5% (95% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 34 publications
(39 reference statements)
4
41
0
Order By: Relevance
“…Previously our group has shown that TB patients have increased levels of HCMV IgG [17] and that HCMV positive infants (as measured by HCMV IFN-c ELISPOT) were at higher risk of progressing to active TB disease [13]. HCMV infection, being linked to poor long-term health outcomes [28,29] and large immune system subversion [16,30], may be acting to manipulate mycobacterial antibodies which may be contributing to protective mechanisms against M.tb infection.…”
Section: Discussionmentioning
confidence: 99%
“…Previously our group has shown that TB patients have increased levels of HCMV IgG [17] and that HCMV positive infants (as measured by HCMV IFN-c ELISPOT) were at higher risk of progressing to active TB disease [13]. HCMV infection, being linked to poor long-term health outcomes [28,29] and large immune system subversion [16,30], may be acting to manipulate mycobacterial antibodies which may be contributing to protective mechanisms against M.tb infection.…”
Section: Discussionmentioning
confidence: 99%
“…89,[130][131][132] A recent meta-analysis suggested a statistical association between CMV infection and an increased risk of CRC. 133 In patients with CRC, CMV RNA transcripts and protein appear to be specifically localized to the cytoplasm of neoplastic mucosal epithelium compared with non-transformed cells. 132,134 The presence of CMV in tumour tissue is associated with an unfavourable outcome in elderly patients with CRC and predicts poor disease-free survival independent of TNM staging.…”
Section: Colorectal Cancermentioning
confidence: 96%
“…Several studies have identified CMV in colorectal cancer (CRC) tissue; about ~ 40% of CRC specimens generally test CMV positive . A recent meta‐analysis suggested a statistical association between CMV infection and an increased risk of CRC . In patients with CRC, CMV RNA transcripts and protein appear to be specifically localized to the cytoplasm of neoplastic mucosal epithelium compared with non‐transformed cells .…”
Section: Cmv‐specific Memory Inflation Shapes Global and Anti‐tumour mentioning
confidence: 99%
“…During active infection, HCMV expresses several proteins, some are essential for its replication and a largr amount may interfere with the cellular and immunological functions, enabling the virus to coexist with its host [5]. Recently, several studies provide evidence that HCMV proteins and nucleic acid has been detected in tissue from several malignancies, including cervical [6], breast [7], colorectal [8], as well as glioblastoma [9] and neuroblastoma [10]. Shanmughapriya et al [11] first found HCMV-glycoprotein DNA by polymerase chain reaction analysis in 50% of tumor tissue specimens from ovarian cancer patients.…”
Section: Introductionmentioning
confidence: 99%